PENGARUH MODEL TEACHING PERSONAL AND SOCIAL RESPONSIBILITY TERHADAP KETERAMPILAN SOSIAL DAN HASIL BELAJAR AFEKTIF - Kurniawan, Rama; Wibowo, Nabilla Kusumaning Nafisa; Darmawan, Arief (Gelanggang Pendidikan Jasmani Indonesia, 2024)
The study examines the influence of the Teaching Personal and Social Responsibility (TPSR) learning model on social skills and emotional learning outcomes. The study used experimental research with randomized pre-test and post-test control group design, Sampling using random sampling techniques of 34 students in experimental groups and 34 students in control classes. Data collection is done using the questionnaire and sheet of affective field values. Based on the analysis of social skills data with the Mann – Whitney Test and the percentage of affective learning outcomes, the results were obtained that there was an influence of the TPSR model on social skills and emotional learning outcomes. Thus, it can be concluded that the TPSR model has an influence on social skills and emotional learning outcomes